From Legal Recognition to Enforcement: Comparative Protection of Workers with Disabilities in Indonesia and Malaysia - Ginting, Ahmad Zaky; Abduh, Rachmad (Universitas Islam Negeri Alauddin Makassar, 2026)
Ensuring equal employment opportunities for persons with disabilities remains a major challenge in many countries, including Indonesia and Malaysia, despite the existence of international standards such as the International Labour Organization (ILO) Convention No. 159 and the United Nations Convention on the Rights of Persons with Disabilities (CRPD). This study examines the regulation and effectiveness of employment protection for workers with disabilities in both countries, particularly regarding the principles of non-discrimination, reasonable accommodation, and access to legal remedies. This research adopts a normative legal approach using statutory, conceptual, and comparative methods. The analysis is based on primary legal materials, including Law No. 8 of 2016 on Persons with Disabilities and Law No. 13 of 2003 on Manpower in Indonesia, as well as the Persons with Disabilities Act 2008 and the Employment Act 1955 in Malaysia, together with international instruments such as the CRPD and ILO Convention No. 159. These materials are analyzed through comparative legal analysis and norm synchronization to evaluate the coherence, enforceability, and institutional mechanisms of disability employment protection in both countries. The findings show that Indonesia demonstrates stronger formal commitments, particularly through constitutional guarantees and a mandatory employment quota for persons with disabilities. However, its effectiveness is limited by regulatory fragmentation, the absence of technical standards for reasonable accommodation, and weak enforcement mechanisms. In contrast, Malaysia lacks a legally binding quota system but provides stronger administrative enforcement and dispute resolution mechanisms, enabling more operational protection in practice. This study contributes to the literature on comparative disability employment law in Southeast Asia by demonstrating that the effectiveness of disability protection depends not only on the existence of legal norms or international treaty ratification but also on regulatory coherence and enforceable institutional mechanisms. The findings highlight the need for regulatory harmonization, stronger enforcement systems, and clear standards for reasonable workplace accommodation to improve the protection of workers with disabilities.